A triple-bottom-line evaluation of municipal solid waste collection - Eirill Bø; Bente Flygansvær (Sustainable Futures)
Municipal Solid Waste (MSW) collection systems can contribute to a sustainable society by transforming waste to valuable resources. However, if not properly designed, the MSW collection systems can become a liability in terms of high cost, high emissions and reduced service. There is still a lack of knowledge on how MSW collection system designs trade off the elements in the triple bottom line. The purpose of this study is to contribute to such understanding. A service-mix framework is proposed, demonstrating trade-offs among the decision areas of bin types, vehicle types, pick-up frequency, delivery distance, co-collection, and sorting in MSW collection systems. The triple bottom line performance is evaluated on cost, service, and emission levels. Two MSW collection systems are analysed and compared, using an Excel-based spreadsheet model. The findings show a potential to improve sustainability in MSW collection systems by trading off service-mix components. Specifically, the findings show that if five households share bins (accept reduced convenience, and the data indicate that they do) the reduction potential is 46 % for cost and 27 % for the CO2 emissions. Similarly, reducing the pick-up frequency service reduces cost and CO2 emissions. Finally, a sensitivity analysis of fill rates shows that using dual chamber trucks gives a high risk of increased cost and CO2 emissions, due to the difficulty of matching waste volumes and chamber sizes. Thus, the paper demonstrates that significant reduction of cost and emission levels are possible without a significant sacrifice of service levels in MSW collection systems.